Non-Communicable Neurological Disorders and Neuroinflammation - Ballerini, Clara; Njamnshi, Alfred K.; Juliano, Sharon L.; Kalaria, Rajesh N.; Furlan, Roberto; Akinyemi, Rufus O. (Frontiers in Immunology, 2022)
Traumatic brain injury, stroke, and neurodegenerative diseases represent a major cause of morbidity and mortality in Africa, as in the rest of the world. Traumatic brain and spinal cord injuries represent a leading cause of disability in the younger population. Stroke and neurodegenerative disorders target the elderly and are a major concern in Africa, since their rate of increase among the ageing is the fastest in the world. Neuroimmunology is not usually associated with non-communicable neurological disorders, as the role of neuroinflammation is not often considered when evaluating their cause and pathogenesis. However, substantial evidence indicates that neuroinflammation is extremely relevant in determining the consequences of non-communicable neurological disorders, both for its protective abilities as well as for its destructive capacity. We review here current knowledge on the contribution of neuroinflammation and neuroimmunology to the pathogenesis of traumatic injuries, stroke and neurodegenerative diseases, with a particular focus on problems that are already a major issue in Africa, like traumatic brain injury, and on disorders that are emerging, such as dementias.